The international journal of meteorology
The International Journal of Meteorology is a bimonthly science magazine on meteorology and severe weather, particularly that of the United Kingdom and Europe. It is a semi-professional non-profit publication with a mix of academic and amateur articles. It is published by Artetech Pub. Co. for TORRO.